'It was the illness talking': self-illness ambiguity and metaphors' functions in mental health narrative - Ervas, Francesca (Philosophical explorations, 2025)
Metaphors may present some challenges in cases of self-illness ambiguity, yet they remain necessary to access a person's perspective on illness and her relationship with it. The paper outlines the main functions of metaphors (i.e., naming, framing, changing functions) to explain why they can be valuable tools for reducing self-illness ambiguity. First, metaphor is presented as a creative way for a patient to (re)claim her 'self' through her own speaker's meaning. Metaphor is not merely a way to name internal processes and make them more communicable to others (compactness and inexpressibility theses), but primarily a way to represent what the mental illness means for herself (for-me-ness thesis). Second, particularly when extended in mental health narratives, metaphor can frame a person's experiences of illness by offering a specific affective perspective for self-understanding (perspectivalness thesis). Third, the changing function of metaphor offers a new perspective on the experience of self-illness ambiguity in the narrative, allowing to look at the relationship with the illness, without fully identifying with it. The metaphorical functions can facilitate the discovery of new forms of affective coherence in a person's mental health narrative and serve as crucial tools for clinicians' understanding in the therapeutic process.